Comment on "Rényi entropy yields artificial biases not in the data and incorrect updating due to the finite-size data" - Jizba, Petr; Korbel, Jan (Physical review. E, 2019)
In their recent paper [Phys. Rev. E 99, 032134 (2019)2470-004510.1103/PhysRevE.99.032134], Oikonomou and Bagci have argued that Rényi entropy is ill suited for inference purposes because it is not consistent with the Shore-Johnson axioms of statistical estimation theory. In this Comment we seek to clarify the latter statement by showing that there are several issues in Oikonomou's and Bagci's reasonings which lead to erroneous conclusions. When all these issues are properly accounted for, no violation of Shore-Johnson axioms is found.